2006
DOI: 10.1038/sj.jp.7211619
|View full text |Cite
|
Sign up to set email alerts
|

The labor induction: integrated clinical and sonographic variables that predict the outcome

Abstract: Objective: To analyze the clinical and sonographic variables that predicts the success of labor induction. Study design:We studied the Bishop score, cervical length and parity in 196 pregnant women in the prediction of successful vaginal delivery within 24 h of induction. Logistic regression and segmentation analysis were performed.Results: Cervical length (odds ratio (OR) 1.089, P<0.001), Bishop score (OR 0.751, P ¼ 0.001) and parity (OR 4.7, P<0.001) predict the success of labor induction. In a global analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 19 publications
1
19
1
10
Order By: Relevance
“…On the other hand, other studies have provided conflicting results (Bueno et al 2007;Chandra et al 2001;Rozenberg et al 2005).…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, other studies have provided conflicting results (Bueno et al 2007;Chandra et al 2001;Rozenberg et al 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Por el contrario, en nuestro estudio, la paridad fue el factor con mayor capacidad predictiva en el resultado de parto. Por ello, decidimos integrarlo en los nuevos índices, coincidiendo con varios autores que también incorporaron la paridad en sus modelos predictivos en gestantes con IDP [10][11][12][15][16][17] . En este sentido, Dhall y col 18 intentaron en 1987 introducir el parámetro de la paridad en una nueva escala formada además por dilatación, borramiento y consistencia.…”
Section: Discussionunclassified
“…The successful vaginal delivery after induction was 70% [69], 75% [70], 89.1% [6]. Bueno et al found that the vaginal delivery occurred in 73.5% of women in the induction group, and the rate of cesarean delivery was 26.5% [18]. Sahanaz et al reported vaginal delivery of 78.9% and 21.1% of cesarean section after induction of labor [56,71].…”
Section: Tripathy and Babymentioning
confidence: 99%
“…Ezechi et al reported the reasons for failed induction with misoprostol include cephalopelvic disproportion, fetal distress, prolong labor, and antepartum hemorrhage [28] Lawani et al also described about fetal distress, prolonged labor, cephalopelvic disproportion as reasons for cesarean section [13]. From the study of Bueno et al, it is understood that the major reasons for cesarean delivery are induction failure (34%), nonreassuring fetal monitoring (28.9%), pelvic disproportion (17%), and failure to progress (14.9%) [18].…”
Section: Tripathy and Babymentioning
confidence: 99%
See 1 more Smart Citation